Tinjauan Yuridis terhadap Kepastian Hukum dalam Proses Pembuktian Perkara Praperadilan di Indonesia - Hendra Abednego Halomoan Purba; Reny Rebeka Masu; Karolus Kopong Medan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The scope of pretrial authority is regulated under Article 77 of the Indonesian Criminal Procedure Code (KUHAP), with an extension of authority introduced through the Constitutional Court Decision Number 21/PUU-XII/2014. The evidentiary process in pretrial proceedings is governed by Article 2 paragraphs (2) and (4) of the Supreme Court Regulation of the Republic of Indonesia Number 4 of 2016 concerning the Prohibition of Judicial Review of Pretrial Decisions. However, in practice, petitions for pretrial often address matters beyond this prescribed authority. Moreover, there remains a disparity in judicial reasoning across different judges, particularly with respect to the evaluation of evidence in the determination of a suspect.The legal issues examined in this study are: (1) whether the expansion of the pretrial authority’s scope has led to multiple interpretations among law enforcement officers, and (2) how the evidentiary process in pretrial proceedings aligns with the principle of legal certainty. This thesis employs normative legal research using statutory, conceptual, and case approaches. The findings of this thesis reveal that the expansion of pretrial authority has indeed created multiple interpretations among law enforcement officials, owing to inconsistencies in pretrial decisions that result from judicial discretion. Furthermore, the evidentiary process in pretrial proceedings ought to be limited to the formal aspects of investigative or prosecutorial actions. Nevertheless, certain pretrial rulings have considered the substance and quality of evidence, and even assessed the conduct of the suspect. Such practices undermine legal certainty for justice seekers. Therefore, the Supreme Court should issue more concrete regulations concerning the scope of pretrial and the evidentiary standards applicable in pretrial proceedings.